(untitled) (Research, Society and Development, 2022)
Objective: To analyze the main protective effects of the influenza vaccine in patients with coronary artery disease. Methodology: This is a systematic review carried out using the PRISMA method, in the electronic databases PubMed, Scopus and Web of Science, using the following descriptors: “influenza vaccines”, “influenza”, “flu”, “coronary artery disease”, “myocardial infarction” and “acute coronary syndrome”. Full articles in Portuguese, English or Spanish published between January 2006 and December 2021 were included; studies that evaluated the effect of influenza vaccine in adult patients (≥18 years of age) with coronary artery disease; studies that included placebo or no vaccine as a control group; studies that reported at least one evaluated outcome and with statistical association. Results: 04 articles composed the final sample of this study. Regarding the approach of the articles found, it was found that three studies used the Randomized Clinical Trial, characterizing the studies as presenting a strong level of evidence (II). In all studies analyzed, influenza vaccine significantly reduced the risk of MACE (cardiovascular death, myocardial infarction, coronary revascularization) compared with the control group. Furthermore, in these studies the influenza vaccine reduced cardiovascular mortality and the risk of acute myocardial infarction. Conclusion: It was found that the influenza vaccine can significantly reduce cardiovascular events in patients with coronary artery disease.